Safety of Red Blood Cell Transfusion Using Small Central Lines in Neonates: An in vitro Non-inferiority Study - Rosa-Mangeret, Flavia; Waldvogel-Abramowski, Sophie; Pfister, Riccardo E.; Baud, Olivier; Fau, Sébastien (Frontiers in Pediatrics, 2021)
AIM: To investigate the safety of transfusing red blood cell concentrates (RBCC) through small (24 Gauge [24G]) and extra-small (28 Gauge [28]) peripherally inserted central catheters (PICC), according to guidelines of transfusion practice in Switzerland. METHODS: We performed a non-inferiority in vitro study to assess the safety of transfusing RBCC for 4 hours at a 4ml/h speed through a 24G silicone and 28G polyurethane PICC lines, compared to a peripheral 24G short catheter. The primary endpoint was hemolysis percentage. Secondary endpoints were catheter occlusion, inline pressure, and potassium and lactate values. RESULTS: For the primary outcome, hemolysis values were not statistically different among catheter groups (0.06% variation, p=0.95) or over time (2.75% variation, p=0.72). The highest hemolysis values in both 24G and 28G PICC were below the non-inferiority predefined margin. We did not observe catheter occlusion. Inline pressure varied between catheters but followed the same pattern of rapid increase followed by stabilization. Potassium and lactate measurements were not statistically different among tested catheters (0.139% variation, p=0.98 for potassium and 0.062%, p=0.96 for lactates). CONCLUSIONS: This study shows that RBCC transfusion performed in vitro through 24G silicone and 28G polyurethane PICC lines is feasible without detectable hemolysis or pressure concerns. Also, it adds that, concerning hemolysis, transfusion of RBCC in small and extra small PICC lines in these is non-inferior to peripheral short 24G catheters. Clinical prospective assessment in preterm infants is needed to confirm these data further.